CT Perfusion to Guide Placement of Invasive Cerebral Perfusion Monitor in Subarachnoid Hemorrhage Induced Vasospasm. (4th April 2018) - Al-Jehani, Hosam; Marcoux, Judith; Hadhiah, Kawthar; Alabbas, Faisal; Angle, Mark; Teitelbaum, Jeanne
Abstract : Background . Vasospasm is a challenging component of the subarachnoid hemorrhage "syndrome" that is unpredictable and very difficult to monitor using noninvasive or invasive monitoring technologies in neurocritical units. Methods. We describe the novel use of computerized tomography perfusion (CTP) imaging to choose proper targets for invasive cerebral blood flow monitors. Results . A total of 3 patients are included in this report. CTP parameters were used to generate points of interest to target using invasive cerebral monitoring of the cerebral blood flow and initiate vasodilator therapy and subsequently guide its weaning. Conclusions . CTP can be useful in localizing a specific anatomical target for invasive monitoring in subarachnoid hemorrhage patients suffering from vasospasm.